Significance of Intellectual Capital reporting to Financial Performance in Telecommunication Companies - Tanti Hafni Arifah Mustofa; Jouzar Farouq Ishak; Arwan Gunawan (Indonesian Accounting Literacy Journal, 2023)
Intellectual capital (IC) is a unique resource related to knowledge and can create added value for the company. IC management as an added value for the company has an influence on financial performance. This research aims to evaluate the influence of IC toward financial performance of telecommunications companies listed on the Indonesia Stock Exchange in 2014-2020. Multiple linear regression analysis and partial also simultaneous hypothesis testing were used to determine the relationship between variables. The results showed a positive relationship between IC and financial performance as measured by ROA, ROE, and EP.